1997
DOI: 10.1177/106907279700500305
|View full text |Cite
|
Sign up to set email alerts
|

The Neurotic Dimension of Vocational Indecision: Gender Comparability?

Abstract: This study examines the relationship between neuroticism and career indecision in separate samples of men and women. College students (151 men, 183 women) constituted the samples. Career indecision was measured by the Career Decision Profile (CDP; Jones, 1989). Constructs used in the study that assess neuroticism included perceived stress, positive and negative affectivity, and state-trait anxiety. In addition, five life history factors predictive of vocational decision-making were also included. Separate clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…The difficulties related to LI can be described as temporary or developmental indecisions and have been used to refer to the normative vocational development phase (Saka & Gati, 2007). Therefore, this type of difficulties could be resolved relatively easily for most adolescents (Meldahl & Muchinsky, 1997), and it reduces during the high school period (Babarović & Šverko, 2016). In contrast, the career indecisiveness that comes from emotionality and other personality-related sources are more chronic and pervasive, and therefore more problematic to deal with in the career counseling process (Saka & Gati, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The difficulties related to LI can be described as temporary or developmental indecisions and have been used to refer to the normative vocational development phase (Saka & Gati, 2007). Therefore, this type of difficulties could be resolved relatively easily for most adolescents (Meldahl & Muchinsky, 1997), and it reduces during the high school period (Babarović & Šverko, 2016). In contrast, the career indecisiveness that comes from emotionality and other personality-related sources are more chronic and pervasive, and therefore more problematic to deal with in the career counseling process (Saka & Gati, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Lounsbury, Tatum, Chambers, Owens, and Gibson (1999) also found that neuroticism was related to indecision. Meldahl and Muchinsky (1997) found that college students with greater negative affect had less knowledge about occupations and training and academic options than their nonneurotic peers. Similarly, Kelly and Pulver (2002) found that neuroticism was related to lack of career information, career choice anxiety, and general indecisiveness.…”
Section: Neuroticismmentioning
confidence: 97%
“…Abusers may prevent women from completing assignments, studying, and purchasing required educational materials. As experiences of negative emotions increase and job or academic performance and evaluations decline, battered women are likely to experience dissatisfaction (Chartrand, Rose, Elliott, Marmarosh, & Caldwell, 1993;Decker & Borgen, 1993;Meldahl & Muchinsky, 1997). Womenand their abusers-may attribute their poor performance to a lack of innate ability and become convinced that, despite their efforts, career and educational success is impossible.…”
Section: Outcome Expectationsmentioning
confidence: 99%